Integrated Curriculum Model in Character Development Based on Sirah Nabawiyah - Niswatin Khoiriyah; Toha Makhshun; Nur Millah Muthohharoh; Evi Fatimatur Rusydiyah (Yayasan Keluarga Guru Mandiri, 2023)
In the 21st century, the curriculum must be developed to prepare better graduates with superior knowledge, character, skills, and critical abilities. The curriculum becomes a tool to achieve the goals of educational institutions. For the curriculum, it is necessary to synergize all aspects of human life. The integrative curriculum as an integrated system is essential in several disciplines and with the realities of human life. This research is explanatory with a case study approach. There were 23 respondents, consisting of the head and teachers of Kuttab Al Fatih (KAF) Sidoarjo, Indonesia. The data analysis used descriptive statistics to analyze responses from questionnaire items. This study finds that the Sirah Nabawiyah-based integrative curriculum shows good results in developing children's character education. Transdisciplinary integration is the philosophical foundation of the development of the KAF curriculum.